Predictors of E-government adoption in India: direct and indirect effects of technology anxiety and information quality. (22nd July 2019) - Kaushik, Kapil; Mishra, Rajhans
E-government adoption has been the focus of many research studies in the past. However, few studies have explored the role of technology anxiety and information quality in the E-government adoption process. The purpose of this paper is to examine the direct and indirect effects of technology anxiety and information quality on E-government adoption. The results of our study indicate that technology anxiety indirectly influences E-government adoption. At the same time, the direct effect of technology anxiety on E-government adoption weakens in the presence of effort expectancy. Perceived information quality has positive direct effect on E-government adoption. However, we did not find any significant indirect effect of information quality on E-government adoption. This study contributes to E-government adoption frameworks by analysing the effect of computer and internet related anxiety and information quality on the adoption of E-government services. Implications for theory and practice that would help the policy makers in enhancing the effectiveness of E-government services have been discussed.